2021
DOI: 10.1080/10717544.2021.2021320
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of a dexamethasone nanosuspension as an intratympanic injection for acute hearing loss

Abstract: Dexamethasone sodium phosphate (Dex-SP) is the most commonly used drug administered via intratympanic injection for the treatment of acute hearing loss, but its penetration efficiency into the inner ear is very low. To address this problem, we evaluated the possibility of administering dexamethasone nanosuspensions via intratympanic injection because hydrophobic drugs might be more effective in penetrating the inner ear. Three types of dexamethasone nanosuspensions were prepared; the dexamethasone nanoparticle… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Figure 3 indicated that NUFS B group showed considerably better hearing at 8 kHz and 16 kHz and very less damage on the organ of corti, because of superior cell membrane permeation and absorption in the tissue than Dex-SP group. 133 Xiao and co-workers synthesized mitochondrial targeting SS31 peptide functionalized GGA loaded poly(lactic-co-glycolic acid) (PLGA) nanocarrier to defend inner hair cell injury caused by gentamicin in zebrafish model. The drug, GGA release profiles of SS31-PEG-PLGA-GGA NPs and PEG-PLGA-GGA NPs specified that amendment of PLGA NPs surface with SS31 peptide did not evocatively change drug release pattern.…”
Section: Aminoglycosides Induced Hearing Lossmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 3 indicated that NUFS B group showed considerably better hearing at 8 kHz and 16 kHz and very less damage on the organ of corti, because of superior cell membrane permeation and absorption in the tissue than Dex-SP group. 133 Xiao and co-workers synthesized mitochondrial targeting SS31 peptide functionalized GGA loaded poly(lactic-co-glycolic acid) (PLGA) nanocarrier to defend inner hair cell injury caused by gentamicin in zebrafish model. The drug, GGA release profiles of SS31-PEG-PLGA-GGA NPs and PEG-PLGA-GGA NPs specified that amendment of PLGA NPs surface with SS31 peptide did not evocatively change drug release pattern.…”
Section: Aminoglycosides Induced Hearing Lossmentioning
confidence: 99%
“…144 Mild or acute noise trauma can be accountable for temporary hearing threshold shift (TTS), [145][146] which can be reversed by regeneration of two different types of hair cell and hearing nerve fiber using glucocorticoid treatment, [147][148] CC BY-NC. 133 whereas overexposure and/ or strong sound vibrations of harmful noise can trigger permanent threshold shift (PTS), resulting to the irreversible HCs regeneration and auditory nerve deterioration, 143,149 Hair cells, especially outer hair cells (OHCs), auditory nerve deterioration, synaptic ribbon reduction and tympanic membrane perforation are the crucial targets of acoustic trauma. [150][151][152] Various studies have evidenced that necrosis and apoptosis detected in the sensory epithelium after exposed to harmful noise trauma, 156 Metal organic framework-based zeolitic imidazolate (ZIF) nano system encapsulated methylprednisolone (MP), MP@ZIF-90 NP was used first time for the treatment of noise-traumatized hearing impairment in preclinical animal model.…”
Section: Noise-induced Hearing Loss (Nihl)mentioning
confidence: 99%
See 1 more Smart Citation